THE IMPORTANCE OF A TEACHER'S PROFESSIONALISM IN IMPROVING THE QUALITY OF EDUCATION IN INDONESIA - Kundaryanti, Fadya Dwi; Rigianti, Henry Aditia (Universitas Syiah Kuala, 2024)
Education is a very planned effort to realize the learning process so that students are active in developing their abilities both in terms of religion, intelligence, noble character, and the skills needed for themselves, society, and the nation and state. To realize the goals of education in Indonesia, there are several main factors, one of which is the professionalism of teachers guiding students in class in learning activities. A professional teacher is a teacher who is able to teach students to become a generation that is able to compete and has good ethics and morals. To be a good educator, it is obligatory to have good character as well. Teacher professionalism plays an important role for students because the teacher is the second parent for students at school so that in any case the form of a teacher's behavior will be exemplified by students and as an educator has a fairly tough task which must be able to educate, direct, as well as motivating students to become students with good character.